Perception Coastal Community on Environmental Pollution in Poka Village Ambon City - Lolita Tuhumena; Basa T Rumahorbo; Sara Umbekna; Friyuanita Lubis; Muhammad Zia Ulhaq Payapo; Pirhel Pirhel; Felycitae Ekalaya Appa; Nicea Roona Paranoan; Winda Ade B Fitriya (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Poka Village, Ambon Bay Distric experiencing significant damage to mangrove ecosystems. There is garbage disposal around the beach of Poka Village. There is garbage disposal around the beach of Poka Village, this has an impact on the ecological and economic functions around the area. Therefore, it is necessary to assess the perception of the behavior of the people around the area and utilize the area. The researcher used 20 respondents as samples and conducted in October to November 2024 on Poka Beach using Random Sampling and using the Likert Scale. Respondents were dominated by women, productive age 45 years, predominantly bachelor degree, with income of IDR 3,000,000 – 4,000,000. Socio-economic characteristics illustrate that respondents live, sell and travel around the area. Respondent characteristics are seen from community perceptions of knowledge of the function of the mangrove ecosystem (3.58) including the strongly agree category, community perceptions of environmental conditions for the growth of the mangrove ecosystem (3.56) including the strongly agree category, community perceptions of the utilization of the mangrove ecosystem (3.35) including the agree. The development of science about public perception that results in environmental pollution to the mangrove ecosystem on Poka beach needs to be known in early countermeasures.